Dielectric properties of liquid phase sintered 0.98BaTiO 3-0.02Ba(Mg1/3Nb2/3)O3 ceramic - Munpakdee A. (2014)
The sintering temperature of 0.98BaTiO3-0.02Ba(Mg 1/3Nb2/3)O3 (BT)(BMN) ceramics was lowered from around 1300 to 900 °C through liquid phase sintering to obtain various microstructural and dielectric properties. The linear shrinkage and densities were recorded and their microstructures were investigated through X-ray diffractometry (XRD) and scanning electron microscopy (SEM). Evolution of the dielectric constant against temperature was measured at various ambient temperatures ranging from room temperature to around 200 °C. The transformation from ferroelectric to paraelectric phase occurred when flux concentration was double the amount used to cause the ceramic ferroelectric state.